The Impact of TPACK and Self-Efficacy on Motivation to Use Technology for Prospective Mathematics Teachers - Mohammad Auzai Aqib; Badrus (Riemann: Research of Mathematics and Mathematics Education, 2026)
In the 21st-century education era, technology integration has become an essential need in mathematics learning. Although the Technological Pedagogical and Content Knowledge (TPACK) framework has become a popular conceptual standard, there remains a research gap regarding how the interaction between technical knowledge (TPACK) and Self-Efficacy simultaneously influences student teachers' motivation to adopt technology. The phenomenon in the field shows that mastery of technology is often not directly proportional to teachers' willingness to implement it in the classroom. This study aims to analyse the impact of TPACK and Self-Efficacy on the motivation of student mathematics teachers in integrating technology into their learning practices. This study uses a quantitative approach with a multivariable regression design. The research subjects consisted of 58 students in mathematics education programs from three universities in Indonesia who were selected through simple random sampling. Data were collected using a Likert-scale questionnaire and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) in SmartPLS 4.0. The main findings indicate that Self-Efficacy has a positive and statistically significant influence on prospective teachers' motivation in using technology (t = 6.27; P < 0.05). In contrast, TPACK did not show a significant direct influence on motivation (P = 0.827). Simultaneously, both variables influenced motivation, with an R2 value of 0.422, indicating that this model explained 42.2% of the variance in motivation to use technology in the moderate category. The results of this study confirm that technical-pedagogical knowledge (TPACK) alone is insufficient to encourage technology adoption without being grounded in an individual's belief in their own abilities. Therefore, teacher education programs should prioritise strengthening Self-Efficacy through structured practice, technology-based teaching simulations, and providing constructive feedback to ensure prospective teachers are not only theoretically competent but also practically motivated.